INSTITUTIONAL FORMS OF SPATIAL PLANNING OF THE AREA OF UNITED TERRITORIAL COMMUNITIES - Stupen Р.; Stupen О. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2022)
It has been studied that the institutional framework for spatial planning is an important tool for ensuring the efficient use of territorial resources for united communities in the framework of decentralization reform. The study shows differences between the structure of planning documentation at all levels in accordance with the current administrative-territorial structure before and after the reform of local self-government and decentralization of power. The importance of planning and development of territories is revealed. It enshrines legal and organizational bases of the town-planning activity for the purpose of maintenance of sustainable development of the territories, self-government on building regulation, ensuring the connection of socio-economic development programs with documentation on spatial planning. The institutional scheme of UTC territory planning at the local level is outlined. It includes development and approval of the general plans of settlements, zoning plans and detailed plans of the territory, as well as a comprehensive plan of spatial development of the territorial community. A comprehensive plan of the spatial development of territorial communities determines the basic principles and directions of formation, which identify the planning organization, functional purpose of the territory, basic principles and directions of formation of a unified public service system, road network, engineering and transport infrastructure, engineering training and landscaping, civil protection and population from dangerous natural and man-made processes, protection of lands and other components of the environment, formation of ecological network, protection and preservation of cultural heritage and traditional environment of settlements, as well as the sequence of decisions, including phased development in accordance with the master plan and a detailed plan of the UTC territory.